Self Disclosure Generasi Z pada Media Sosial TikTok - Hidayat, Mochammad Alwi (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2023)
The use of social media in Indonesia can be categorized at a high level. Generation Z is a generation that is more interested in the internet compared to other groups. This is supported by a survey by the Alvara Research Center which shows that generation Z is included in the internet addiction category with a usage duration of 7-10 hours a day at 20.9%. TikTok is the social media that has been used the longest by the public. This research aims to determine the forms of self-disclosure carried out by generation Z, the causal factors, social implications, and analyze them based on uses and gratification theory, self-disclosure theory, and Maslow's hierarchy theory. The method used in this research is descriptive qualitative by conducting interviews, observations and literature studies. Then, based on the research results, they were analyzed using the Milles & Huberman technique. From the results of this research, it was found that the forms of self-disclosure carried out by generation Z vary according to the "Johari Window" concept, the causal factor is because generation Z's need for social media TikTok is in accordance with the uses and gratification theory, and the social implications of self-disclosure are to fulfill The basic human need for establishing social relationships on TikTok is in accordance with Maslow's hierarchy theory